Acute hypoglycemia and risk of cardiac arrhythmias in insulin-treated type 2 diabetes and controls. Issue 2 (21st July 2021) - Andersen, Andreas; Bagger, Jonatan I; Baldassarre, Maria P A; Christensen, Mikkel B; Abelin, Kirsten U; Faber, Jens; Pedersen-Bjergaard, Ulrik; Holst, Jens J; Lindhardt, Tommi B; Gislason, Gunnar; Knop, Filip K; Vilsbøll, Tina
Abstract : Objective: Hypoglycemia is associated with an increased risk of cardiovascular disease including cardiac arrhythmias. We investigated the effect of hypoglycemia in the setting of acute glycemic fluctuations on cardiac rhythm and cardiac repolarization in insulin-treated patients with type 2 diabetes compared with matched controls without diabetes. Design: A non-randomized, mechanistic intervention study. Methods: Insulin-treated patients with type 2 diabetes ( n  = 21, age (mean ± s.d.) : 62.8 ± 6.5 years, BMI: 29.0 ± 4.2 kg/m 2, HbA1c: 6.8 ± 0.5% (51.0 ± 5.4 mmol/mol)) and matched controls ( n  = 21, age: 62.2 ± 8.3 years, BMI 29.2 ± 3.5 kg/m 2, HbA1c: 5.3 ± 0.3% (34.3 ± 3.3 mmol/mol)) underwent a sequential hyperglycemic and hypoglycemic clamp with three steady-states of plasma glucose: (i) fasting plasma glucose, (ii) hyperglycemia (fasting plasma glucose +10 mmol/L) and (iii) hyperinsulinemic hypoglycemia (plasma glucose < 3.0 mmol/L). Participants underwent continuous ECG monitoring and blood samples for counterregulatory hormones and plasma potassium were obtained. Results: Both groups experienced progressively increasing heart rate corrected QT (Fridericia's formula) interval prolongations during hypoglycemia ((∆mean (95% CI): 31 ms (16, 45) and 39 ms (24, 53) in the group of patients with type 2 diabetes and controls, respectively) with similar increases from baseline at the end of the hypoglycemic phase ( P = 0.43). The incidence of ventricular premature beats increased significantly in both groups during hypoglycemia ( P = 0.033 and P < 0.0001, respectively). One patient with type 2 diabetes developed atrial fibrillation during recovery from hypoglycemia. Conclusions: In insulin-treated patients with type 2 diabetes and controls without diabetes, hypoglycemia causes clinically significant and similar increases in cardiac repolarization that might increase vulnerability for serious cardiac arrhythmias and sudden cardiac death.